3D Bioprinting: An attractive alternative to traditional organ transplantation - Darakhshanda Iram; Rafi a Riaz; Rana Khalid Iqbal (Archive of Biomedical Science and Engineering - Peertechz Publications, 2019)
3D bioprinting is computer-aided technology used to generate 3D models of organs. Employing this technique, organ and tissues are generated according to the patient body. 3D structures are formed by the deposition of bioink. This bioink can be natural or synthetic bionink. For in vitro implantation, the tissue is first incubated in a bioreactor, however, in in vivo there is no prerequisite incubation required, rather cells are directly implanted. Bioprinting consists of various steps involving imaging, design approach, choice of material, cell selection and printing of tissue construct.3D bioprinting has two main approaches, i.e. cellular and a-cellular. Cellular bioprinting can be inkjet based, stereolithography based, laser induced forward transfer (LIFT) and extrusion based. Acellular bioprinting is extrusion based and laser based. Tissues of various organs are formed using 3D bioprinting involving blood vessels, bone, cartilage, heart, kidneys, and that of the skin and neurons. However, bioprinting of micro organs and the selection of suitable bioink is a diffi cult task. Bioprinting has various limitations that lead to the development of 4D bioprinting. This review paper will help you to understand the basic technique of 3D bioprinting, its application, limitations and new advancements that help to enhance the effi cacy of this technique.